Analysis on Bacterial Community of Noctiluca scintillans Algal Blooms Near Pingtan Island, China - Yunguang Liu; Yutong Zhang; Haiyan Yao; Zewen Zheng; Wenbo Zhao; Gang Lin (Biology)
Noctiluca scintillans, known as a global red tide species, is a common red tide species found in Pingtan Island. To examine the bacterial community structure in different environments during the red tide period of N. scintillans on Pingtan Island, samples were collected from the Algal Bloom Area (ABA), Transition Area (TA), and Non-Algal Bloom Area (NBA) on 6 April 2022, and the environmental physicochemical factors and bacterial community were determined. The outbreak of N. scintillans red tide significantly impacted the water quality and bacterial community structure in the affected sea area. The water quality in the ABA has deteriorated markedly, with the contents of COD, NH4+-N, and PO43− in the ABA being significantly higher than those in the TA and NBA, while the pH is significantly lower than that in the TA and NBA. The richness, diversity, and evenness of the bacterial community in the ABA are all lower than those of the TA and NBA. For instance, the Shannon index values of the three sampling points are 4.41, 5.41, and 6.37, respectively. At the phylum level, the dominant bacterial phyla in the ABA are Proteobacteria, Firmicutes, and Cyanobacteria; in the TA, they are Proteobacteria, Bacteroidetes, and Firmicutes; and in the NBA, they are Proteobacteria, Bacteroidetes, and Cyanobacteria. At the genus level, the dominant bacterial genera in the ABA are Vibrio, Carnobacterium, Candidatus_Megaira, Planktomarina, and Pseudoalteromonas; in the TA, they are Vibrio, Planktomarina, Lentibacter, Glaciecola, and Jannaschia; and in the NBA, they are Planktomarina, Amylibacter, NS5_marine_group, Aurantivirga, and marine_metagenome. In the ABA, the combined proportion of Vibrio and Carnobacterium exceeds 50%, with Vibrio_splendidus accounting for 93% of the total Vibrio population. These research results can provide a scientific basis for clarifying the environmental characteristics and bacterial composition during the large-scale N. scintillans red tide in Pingtan Island.